Diagnosys of prevalent nursing and cautions prescribed to orthopedical patients. A descriptive study - Miriam Abreu Almeida; Vanessa Kenne Longaray; Paula de Cezaro (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
This is a descriptive, retrospective study based on statistics, in which the aim is to identify the nursing cautions prescribed and its periodicity for the three major diagnosis shown by orthopedical patients that had to undergo surgery for total knee or hip replacement, at the Porto Alegre Clinics Hospital, in 2003. The project was approved by the Ethics and Health Research Comitee from that Institution. The data was obtained by computerized records and analyzed using descriptive statistics. As a result, 170 patients went through the surgery abobe mentioned, showing 36 different nursing diagnosis, being Deficit in Self-care: shower and/or higiene, Impaired Physycal mobility and Infection risk the three that occurred most often, in 52 of the cases handled.The computerized prescription system of the HCPA reflects the practice of the nurse. The data inserted in the system needs constant reviewing and permanent education from the nurses. Trata-se de um estudo quantitativo retrospectivo descritivo objetivando identificar os cuidados de enfermagem prescritos e suas freqüências para os três diagnósticos de enfermagem (DE) prevalentes apresentados por pacientes ortopédicos adultos submetidos a Artroplastia Total de Quadril (ATQ) ou Joelho (ATJ), no Hospital de Clínicas de Porto Alegre em 2003. O projeto foi aprovado pelo Comitê de Ética e Pesquisa em Saúde da Instituição. Os dados foram obtidos através dos registros informatizados fornecidos pelo Grupo de Sistemas da Informação e analisados por meio de estatística descritiva. Como resultado, 170 pacientes foram submetidos às cirurgias apresentando 36 DE, sendo Déficit no Auto-Cuidado: banho e/ou higiene, Mobilidade Física Prejudicada e Risco para Infecção os três prevalentes. O sistema de prescrição informatizada do HCPA reflete a prática da enfermeira. Os dados inseridos no sistema necessitam de constante revisão, além de educação permanente dos enfermeiros.